Coverage control for heterogeneous mobile sensor networks with bounded position measurement errors - Song, Cheng; Liu, Lu; Feng, Gang; Fan, Yuan; Xu, Shengyuan (Automatica (Oxford), 2020)
The coverage control problem for a network of heterogeneous mobile sensors with bound position measurement errors on a circle is addressed in this paper. A practical measurement error model is considered in which only the upper bounds of the measurement errors are known by the sensors a priori. The coverage cost function is defined as the largest arrival time from the mobile sensor network to any point on the circle. Two cases of coverage control with and without order preservation of the sensors respectively, are considered. For each case, the upper bounds on the measurement errors are employed to design an estimation algorithm for each sensor to estimate the difference between neighboring sensors’ positions. Then, distributed coverage control laws are developed for the mobile sensors by using the estimated difference. Under the proposed control laws, the sensor network is driven to a neighborhood of the optimal configuration minimizing the cost function and the effect of the measurement errors on the coverage performance is reduced or even eliminated.